2020
DOI: 10.1111/jbfa.12451
|View full text |Cite
|
Sign up to set email alerts
|

Good for managers, bad for society? Causal evidence on the association between risk‐taking incentives and corporate social responsibility

Abstract: Using FAS 123R as an exogenous shock to stock options, I provide evidence that equity‐based risk‐taking incentives discourage corporate social responsibility (CSR). This finding suggests that compensation incentives can motivate managers not to pursue CSR strategies because CSR reduces firms’ risk and provides insurance‐like benefits. Firms with a greater demand for CSR's risk reduction are more sensitive to changes in risk‐taking incentives. I triangulate my results by confirming that CSR weaknesses are posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 122 publications
(155 reference statements)
0
23
0
Order By: Relevance
“…Alternatively, risk-tolerant CEOs may be better able to ignore litigation risks that result from incomplete or unclear CSR disclosures compared with their less risk-tolerant counterparts. In fact, Mayberry (2020) found that CEOs' risk-taking incentives are negatively associated with CSR. Given that information is costly and public disclosures may reveal inside information to competitors, CEOs with high risk tolerance are more likely to disregard the risk that stakeholders may be unable to fully utilize the CSR information supplied.…”
Section: Hypothesis Development: Relationship Between Ceos' Personality and Csr Reportingmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, risk-tolerant CEOs may be better able to ignore litigation risks that result from incomplete or unclear CSR disclosures compared with their less risk-tolerant counterparts. In fact, Mayberry (2020) found that CEOs' risk-taking incentives are negatively associated with CSR. Given that information is costly and public disclosures may reveal inside information to competitors, CEOs with high risk tolerance are more likely to disregard the risk that stakeholders may be unable to fully utilize the CSR information supplied.…”
Section: Hypothesis Development: Relationship Between Ceos' Personality and Csr Reportingmentioning
confidence: 99%
“…Capital-providing stakeholders may require managers to invest in riskier projects with higher growth potential and higher financial returns, whereas other stakeholders may want managers to reduce risk by investing in CSR (Chakraborty et al, 2019). CSR investment is perceived to be risk reducing as it helps firms build reputational and moral capital (Mayberry, 2020) and therefore negatively correlates with CEOs' risk-tolerant personality or risk-taking incentives.…”
Section: Hypothesis Development: Relationship Between Ceos' Personality and Csr Reportingmentioning
confidence: 99%
“…However, its effect on CSR engagement is relatively less clear. Recently, few studies have focused on the CEO's delta (or vega) as a potential determinant of a firm's CSR engagement (Mayberry, 2020; McGuire et al, 2019) or the relationship between CEO's incentive and CSR (Ben‐Amar et al, 2021; Flammer et al, 2019; Peng, 2020). Nevertheless, to the best of our knowledge, our study is the first attempt to separately examine the effect of CEO's wealth alignment with shareholders (proxied by the CEO's delta) on the strength and concern CSR activities for external and internal stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, CEOs with a large vega have no incentive to invest in CSR activities; thus, we expect a negative effect (or no effect) of Vega on CSR engagement (i.e., β 2 < 0 or β 2 ¼ 0). Recently,Mayberry (2020) finds supportive evidence for the negative effect of Vega on CSR engagement. However, even according to this line of thought, Vega can induce CSR engagement (i.e., β 2 > 0) as CSR's insurance-like benefits can allow CEOs with a large vega to take high-risk projects more aggressively.…”
mentioning
confidence: 98%
“…It is highly argued that CSR activities decrease stock price crash risk and firm default risk [180,[204][205][206][207]. In fact they are based on controlling and avoiding risk-taking mechanisms [125,208] and designed to avoid harming stakeholders through pollution prevention practices and fair-trade policies [179,209].…”
Section: Risk Mitigationmentioning
confidence: 99%